Chronic recurrent multifocal osteomyelitis of the first metatarsal bone: a case report - Chiu, Chee Kidd; Singh, Vivek Ajit (SAGE Publications (UK and US), 2009)
We report a case of chronic recurrent multifocal osteomyelitis in a 9-year-old girl. She presented with a 9-month history of gradually worsening pain and swelling in her left foot. Non-steroidal anti-inflammatory drugs were prescribed but the symptoms persisted. She underwent curettage through a small oval corticotomy window on the first metatarsal bone. The pain and swelling improved promptly and she was able to walk without pain 2 weeks later. Curettage enabled rapid symptomatic relief and induced remission, with little risk of complications.